Family and community partnerships : promising practices for teachers and teacher educators - Caspe, Margaret; Hernandez, Reyna; Mapp, Karen L.; Borrello, Vito J. (Emerald Publishing Limited : IAP | Information Age Publishing Inc, 2023)
"Family and Community Partnerships: Promising Practices for Teachers and Teacher Educators, offers a fresh new look at the competencies, strategies, and practices that effective educators develop to build strong partnerships with families and communities. Written by leaders in the field, the book is an outgrowth of a cutting-edge initiative led by the National Association for Family School and Community Engagement to reimagine how educators are prepared for family and community engagement. Based on four guiding practices - reflect, connect, collaborate, and lead alongside families - each section of the book highlights theory, real-world strategies, discussion questions, and activities that can be used by teachers, teacher educators, and professional learning specialists to inspire new ideas for courses, workshops, and for self-reflection"-- Provided by publisher.
Keywords: Community and school -- United States.; Home and school -- United States.; School improvement programs -- United States.; Teachers -- Training of.; Education -- Parent Participation.; elektronické knihy; electronic books